Clinicomycological study of pityriasis versicolor - Anaz, K K; Vineetha, Mary; Celine, MI (Asian Journal of Medical Sciences, 2022)
Background: Pityriasis versicolor (PV) is a mild chronic infection of the skin caused by Malassezia yeasts, and characterized by discrete or confluent scaly, discolored or dyspigmented areas, mainly on the upper trunk. Wood’s lamp examination and potassium hydroxide (KOH) smear are essential tools to diagnose certain cases of PV. KOH smear examination is simple but may be difficult to interpret sometimes. Lactophenol cotton blue (LPCB) mount helps to visualize the hyphae and spores more clearly4. Hence, this study was conducted to assess the clinical features, epidemiological factors as well as KOH smear and LPCB findings in cases of PV. Aims and Objectives: To study the clinicomycological and epidemiological profile of PV in patients attending the department of Dermatology and Venereology, Government medical college, Kottayam. Materials and Methods: A descriptive cross-sectional study was done for a period of 18 months. All clinically diagnosed cases of PV were included in the study. A detailed history taking and clinical examination to asses the epidemiological parameters and to find any predisposing factors was done. Scrapings were taken for KOH smear demonstration and LPCB mount. The characteristics of hyphae were studied. Results: Peak incidence of disease was seen in 2nd and 3rd decade with a male preponderance. Most of the patients were asymptomatic with hypopigmented type on the trunk with positive stretch sign. Seborrheic dermatitis was the most common association. KOH mount and LPCB stain demonstrated hyphae in more than 90%. Conclusion: PV is a disease of younger age with hypopigmented macule on trunk being the commonest presentation. KOH mount and LPCB stain are useful tool in diagnosis.